Golden Age: Pendidikan Inklusi Berbasis Budaya di Lingkungan PAUD Lab. FIP UNY Pedagogia - Laily Rizqina, Aulia (ACIECE, 2019)
This article discusses cultural-based inclusive education in early echildhood. This research wasconducted at the PAUD Lab. UNY Pedagogia where cultural based inclusive education in ealrychildhood is carried out in the process of learning and playing activities in instilling cultural values in ealy childhood. The inculcation of cultural values in inclusive education is also carried out by the school through traditional games. The process of learning and playing in instilling culture in teacher students uses the habituation method. The cultual values that are instilled in early childhood in PAUD Lab. UNY Pedagogia including, Tepo Sliro, Ungguh-Ungguh, Andhap Ashor, Gugur Gunung, Welas Asih, Tertib, Tekun, dan Nerimo Ing Pandum. The nature of this research is descriptive qualitative which describes the condition of the object studied contextually as the results of the data obtained through interviews and observations at the research location